Quality Management of the Activities of Sports Schools - Hasiuk, Ihor (Pedagogical Discourse, 2015)
The article examines the process of quality management of the activities of sports schools. The content of the regulatory framework of quality management at the level of the operational core, direction and control functions of management of separate operating unit have been nvestigated. The content of the system components of the quality management of activities of the object of management has been determined. The conceptual scope of the category of «quality management of the activities of sports school» has been defined, on the basis of the establishment of the content of functions of management of the sports school. The corner principles of the process of quality management have been characterized, and the content matrix of sub processes of management according to guaranteeing activity of sports school has been outlined.